Targeting gut microbiota dysbiosis in inflammatory bowel disease: a systematic review of current evidence - Farah, Asmaa; Paul, Pradipta; Khan, Anfal Sher; Sarkar, Aparajita; Laws, Sa’ad; Chaari, Ali (Frontiers in Medicine, 2025)
IntroductionThe dysbiosis of the gut microbiota has been identified as a central factor in the pathogenesis of inflammatory bowel disease (IBD), a chronic condition characterized by frequent recurrence and various adverse effects of traditional therapies. While treatments targeting the gut microbiota show promise, their efficacy in IBD management still requires extensive evaluation. Our systematic review analyzes recent studies to elucidate the advancements and challenges in treating IBD using microbial-based therapies.MethodsThrough a comprehensive systematic review spanning key scientific databases—PubMed, Embase, Cochrane, Web of Science, Scopus, and Google Scholar—we scrutinized the impact of probiotics, prebiotics, synbiotics, and fecal microbiota transplantation (FMT) on individuals with IBD. Our detailed analysis covered study and participant demographics, along with seven key outcome measures: disease activity index, inflammatory markers, serum cytokines, microbiome composition, adverse effects, and the rates of remission and relapse.ResultsFrom 6,080 initial search hits, we included 71 studies that assessed various interventions compared to placebo or standard medical therapy. Although there was notable variation in clinical results while assessing different outcomes, overall, probiotics, prebiotics, and synbiotics enhanced the success rates in inducing remission among IBD patients. Furthermore, we noted significant reductions in levels of pro-inflammatory markers and cytokines. Additionally, the requirement for steroids, hospitalization, and poor outcomes in endoscopic and histological scores were significantly reduced in individuals undergoing FMT.ConclusionOur investigation highlights the potential of targeting gut microbiota dysbiosis with microbial-based therapies in patients with IBD. We recommend conducting larger, placebo-controlled randomized trials with extended follow-up periods to thoroughly assess these treatments’ clinical efficacy and safety before widespread recommendations for clinical application.